TPR 13 - Use of Vertical Boreholes for Assisting Ventilation of Longwall Gob Areas - C. H. Elder (The National Institute for Occupational Safety and Health (NIOSH), 1969)
An experimental degasification program using a vertical borehole and vacuum pump to drain gas from the gob area of a longwall panel was successful at Bethlehem Mines Corporation, Cambria Division, No. 33 coal mine. Sixty-one million cubic feet of methane has been exhausted during a 9-month period. Daily production time in the panel increased as a result of lower methane levels in the returns. Removal of large quantities of methane in this way and the exclusion of it from the ventilating system will provide reduced cost in mine ventilation and provide a safer environment for the mine.